A novel source of atomic hydrogen for passivation of defects in silicon. Issue 5 (27th February 2017) - Hamer, Phillip; Bourret‐Sicotte, Gabrielle; Martins, George; Wenham, Alison; Bonilla, Ruy S.; Wilshaw, Peter
Abstract : Palladium membranes have been used for decades for the separation of hydrogen from other gasses. In this letter the use of thin palladium leaves to act as sources of atomic hydrogen for silicon samples is explored. It has been assumed in the past that although hydrogen diffuses through palladium in atomic form, the atoms recombine to form molecular hydrogen at the surface. In this letter it is shown that hydrogen supplied to one surface of a palladium leaf can result in atomic hydrogen being released from the opposite surface at low pressure. This is demonstrated through the use of a palladium leaf in a direct plasma system which allows for atomic hydrogen to be supplied to a sample while avoiding exposure to UV radiation from the plasma and high energy charged particles. This method is shown to provide significant atomic hydrogen to silicon samples and improve passivation of silicon surfaces. Method of Shielded Hydrogen Passivation: Schematic of direct plasma chamber with a shield inserted between the plasma and the silicon sample. Abstract : This letter details a new approach for introducing atomic hydrogen to silicon samples, dubbed shielded hydrogen passivation. This method involves placing a thin metallic "shield", in the current work a 100 nm palladium leaf, between a plasma hydrogen source and the sample. This shield prevents any damage to the samples from UV radiation or energetic particles, while still providing effective hydrogen passivation.